Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

Solve the following quadratic by
completing the square.
y = x2 - 6x + 7



Sagot :

Answer:

x = 5  or   x = 1

Step-by-step explanation:

 x² - 6x + 7 = 0

x² - 6x = -7

x² - 6x + 9 = -7 + 9      1/2 of the x term than square it and add it the both sides.

(x - 3)(x - 3) = 2

( x -3)² = 2

[tex]\sqrt{(x - 3)^2[/tex] = [tex]\sqrt{2}[/tex]

(x -  3) = ± 2

x - 3 = 2  or  x - 3 = -2

x = 5     or  x = 1

Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.